TELAAH KONSEPTUAL RELATIONSHIP MARKETING DAN PERKEMBANGANNYA - Febrian Humaidi Sukmana; Sri Maryanti (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2019)
Many academics and practician of marketing admit that Relationship Marketing (RM) has developed vastly and also considered contributed to paradigm reformation, it even become the basis of marketing science theory reform. Hence, discussion on RM is interesting to be studied. The study aimed to synthesize various opinion and former research result to get a clearer view for academics, manager and general reader concerning concept of RM. Various literatures, either periodic journals, conference articles and textbooks are collected and used as references in this monography. Writer find out some perspectives used by scientists to describe RM concept, start from marketing philosopny aspect, resources based perspective, marketing strategy, value creation and mutual value creation (value co-creation). Writer concluded that various perspectives applied in formulating RM is strengthen the other perspective. Despite seems to be overlapped but there’s a link that connected each perspective. Writer thought that (theoretically) value co-creation is the most relevant perspective to outlines RM process and activities in today’s situation. Whereas in field, many corporates placed RM as one of their main strategy in marketed the company.